2015
DOI: 10.2169/internalmedicine.54.4068
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis as a Possible Indicator of Pancreatic Cancer: The Importance of Mass Detection

Abstract: Objective The aims of this study were to assess the incidence of pancreatic cancer and the contributing factors for the diagnosis of tumors in patients with acute pancreatitis and to gain insight into how patients with acute pancreatitis should be followed up. Methods Using the electronic medical database of Shizuoka General Hospital, 177 patients admitted for acute pancreatitis in the past 6 years were evaluated retrospectively for pancreatic cancer. Results Twelve patients (6.8%) were newly diagnosed with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
(32 reference statements)
1
27
0
4
Order By: Relevance
“…The rate of AP in PC patients varies widely and has been reported to range from 6.8% to 13.8%. [ 6 , 7 ] Abdominal pain, weight loss, and jaundice were the main symptoms in patients with AP. We observed that abdominal pain occurred in 47 (100%) patients, jaundice in 4 (8.5%), and weight loss in 16 (34.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of AP in PC patients varies widely and has been reported to range from 6.8% to 13.8%. [ 6 , 7 ] Abdominal pain, weight loss, and jaundice were the main symptoms in patients with AP. We observed that abdominal pain occurred in 47 (100%) patients, jaundice in 4 (8.5%), and weight loss in 16 (34.0%).…”
Section: Discussionmentioning
confidence: 99%
“…They believed that AP recurring after IPMN resection was the result of sudden obstruction of the main duct by abundant mucus secretion. Moreover, Kimura et al [ 6 ] reported that PC may produce some chemical mediators, which may be responsible for AP. However, in our study, not all the cases present with dilatation of main pancreatic duct (6 patients).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest sample of PC in patients with AP using ICD-10 for the year 2016. There has been varied reported incidence of AP in PC patients in the range between 6.8% and 13.8% [17].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The frequency of AP in pancreatic cancer patient has been reported to vary from 6.8% to 13.8% and majority of patients present with mild AP. [4][5][6] The ductal adenocarcinoma causes AP by obstructing the main PD, producing ductal hypertension, and consequent leakage of enzymes. These patients are usually misdiagnosed and the underlying malignancy…”
Section: Discussionmentioning
confidence: 99%